Women in physics: A comparison to science, technology, engineering, and math education over four decades - Linda J. Sax; Kathleen J. Lehman; Ramón S. Barthelemy; Gloria Lim (Physical Review Physics Education Research, 2016)
[This paper is part of the Focused Collection on Gender in Physics.] The dearth of women in science, technology, engineering, and math (STEM) fields has been lamented by scholars, administrators, policymakers, and the general public for decades, and the STEM gender gap is particularly pronounced in physics. While previous research has demonstrated that this gap is largely attributable to a lack of women pursuing physics in college, prior research reveals little in terms of the characteristics and career interests of women who do plan to major in physics or how these traits have evolved over time. To address these gaps, this study utilized nationwide data on first-time, full-time college students to (1) document national trends in plans to major in physics among women entering college, (2) document the career aspirations of women who intend to major in physics, and (3) explore the characteristics of women who intend to major in physics and how this population has evolved across time. This study found that women’s interest in physics has been consistently very low in the past four decades. The most popular career aspiration among women who plan to major in physics is research scientist, although this career aspiration is declining in popularity, while increasing numbers of women say that they are undecided in their career choice. Further, this study identifies a distinctive profile of the average female physics student as compared to women in other STEM fields and women across all majors. Women who plan to pursue a physics major tend to be confident in their math abilities, value college as an opportunity to learn, plan to attend graduate school, and desire to make theoretical contributions to science. However, they are less likely than women in other fields to have a social activist orientation. These findings have important implications for scholars, educators, administrators, and policymakers as they seek to recruit more women into the physics field.